Pengaruh Tingkat Pengetahuan Industri Batik Menuju Industri Hijau sebagai Bentuk Tanggung Jawab Sosial pada Keberlanjutan Lingkungan - Maghfiroh Maghfiroh; Wenti Ayu Sunarjo; Aditya Dimas Wahyu Sasongko; Nila Oktaviani; Ristiawati Ristiawati; Faiz Tyas Hanifah; Wafa Khanza Fadhilah (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
One of the impacts following the inauguration of Indonesian Batik as an intangible cultural heritage by UNESCO in 2009 was that many batik businesses emerged in various regions. This increase can increase the amount of production and at the same time have an impact on the environment. The presence of government regulations regarding the green industry for the batik industry has allegedly not been a concern for batik entrepreneurs, especially in Pekalongan City. Most of the batik industry still implements production processes without paying attention to SMK3 and environmental aspects, so the aim of this research is to measure the level of knowledge of the Pekalongan City batik industry regarding the existence of government regulations relating to green industry standards for the batik industry. The method used is a survey method using a quantitative approach. Furthermore, the impact of this research can be a reference for the government to provide stimulus and treatment for batik SMEs in increasing knowledge about Permenperin No. 10 of 2023 for the batik industry towards a more focused green industry through green industry certification for batik SMEs.